Global warming and impact on Indian agriculture and food production - Palanichamy, A.P. (Food Biology, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Global warming refers to an average increase in the earth’s temperature, which in turn courses in climate, Contribution of greenhouse gases to global warming, carbon dioxide, methane, Chloro-Fluro-Carbon (CFCs) and Nitrous oxides act like a green house, warming the earth surface. The rise in earth’s temperature due to increase in carbon dioxide emission has been speculated since 1800’s and its effect house been analysed. The foremost cause for transformation of global environment is the ever increasing number of human beings since 1990, the number of people has more than tripled. According to UN projection, the global population increased from 205 billion to 5 billion in less than four decades (i.e.) from 1950 to 1990 and is expected to reach 10 billion by the end of next century. Developing countries account for only 1.29 billion tones of CO2 emission 1985 and projected increase for 2005 in 5.47 billion tonnes of carbon oxide was emitted with is projected to increase to 12.18 billion tones by 2025. The CO2 emissions are projected to increase by 2.6 percent annually.